(untitled) (Lapai Journal of Economics, 2023)
The study was conducted to assess the impact of risk management regulations on the financial performance of Microfinance Institutions (MFIs) in Tanzania. Specifically, the study was guided by a descriptive research design. The target population of this study included Microfinance Institutions (Tier 1 Microfinance Institutions) in Tanzania where all three (3) MFIs were selected. The study employed secondary data collected from the MFIs yearly annual reports from 2019 to 2022 and Bank of Tanzania (BOT) published statistics on MFIs. The study used a panel data random effect model to establish the relationship between risk management regulations and MFIs financial performance. The study found capital adequacy ratio requirements (CAR) to statistically positively influence the financial performance of the MFIs while the cash reserve requirements (CRR) statistically negatively influence the financial performance of the MFIs and liquidity ratio requirements (LRR) do not significantly influence the financial performance of the MFIs.The study concluded that MFIs should continue adhering to the available policy and regulations so as to evade exposed risks. Moreover, in terms of capital adequacy and cash reserve requirements, the BOT should set minimum capital depending on the risk capabilities of the MFIs. Furthermore, our study recommended that BOT should ensure that all MFIs adhere to the written policy and procedures to mitigate the operational, financial, and strategic risks among the MFIs.